The influencing factors on procalcitonin values in newborns with noninfectious conditions during the first week of life - Jueseong Lee; Yong Hyeon Bang; Eun Hee Lee; Byung Min Choi; Young Sook Hong (Korean Pediatric Society, 2017)
PurposeAlthough procalcitonin (PCT) level is useful for the diagnosis of neonatal sepsis, PCT reliability is inconsistent because of the varied conditions encountered in neonatal intensive care units. This study aimed to investigate PCT levels and factors influencing increased PCT levelin newborns without bacterial infection during the first week of life.MethodsIn newborns hospitalized between March 2013 and October 2015, PCT levels were measured on the first, third, and seventh days after birth. Newborns with proven bacterial (blood culture positive for bacteria) or suspicious infection (presence of C-reactive protein expression or leukocytosis/leukopenia) were excluded. Various neonatal conditions were analyzed to identify the factors influencing increased PCT level.ResultsAmong 292 newborns with a gestational age of 35.2±3.0 weeks and a birth weight of 2,428±643 g, preterm newborns (n=212) had higher PCT levels than term newborns (n=80). Of the newborns, 7.9% had increased PCT level (23 of 292) on the firstday; 28.3% (81 of 286), on the third day; and 3.3% (7 of 121), on the seventh day after birth. The increased PCT level was significantly associated with prenatal disuse of antibiotics (P=0.004) and surfactant administration (P<0.001) on the first day after birth, postnatal use of antibiotics (P=0.001) and ventilator application (P=0.001) on the third day after birth, and very low birth weight (P=0.042) on the seventh day after birth.ConclusionIn newborns without bacterial infection, increased PCT level was significantly associated with lower gestational age and respiratory difficulty during the first week of life. Further studies are needed for clinical applications.